Cabaran dalam komunikasi sukarelawanan - Haslinda, Hashim; Abdullah Adnan, Mohamed (Program Pemindahan Ilmu Transformasi Belia (Trans-B), 2014)
Encik Khoo Yeoh Gan Hong, Pengerusi Settlement Youth Council bagi penggal 1956-1957, dalam ucapan sulung beliau selepas dipilih selaku Pengerusi pada 5 Mei 1957 menyatakan bahawa, “Within a few months we shall welcome a new era in the history of this country. We must be prepared to face and accept greater challenges and responsibilities. To this end let us pray for a strong back rather than for a light burden. As youth leaders and workers of all races, classes and creeds, may we be given the strength to spread the spirit of the brotherhood, goodwill and tolerance and may our personal examples be worthy of emulation” (Misni Surif, Mohamed Maliki Mohamed Rapiee & Ishak Saat (2008) 60 Tahun Perjalanan Majlis Belia Negeri Pulau Pinang, 1948-2008.)